Conciencia ambiental de los pobladores de la zona urbana y el caserío Quistococha del distrito de San Juan Bautista. 2021 - Saavedra Zegarra, Sharen Cristina (2022)
The intention of this research was to confront the environmental awareness of the inhabitants of the urban area (represented by the surroundings of the central part of San Juan Bautista) and peri-urban area (Quistococha community) in the district of San Juan Bautista. The objective was to compare the environmental awareness of the inhabitants of the urban and peri-urban area (Quistococha community) of the District of San Juan. The non-experimental, quantitative, cross-sectional research design was used. With a simple probabilistic sample, where 158 people were selected, 85 from the urban area and 73 from the peri-urban area. The results obtained from the surveys were demonstrated through descriptive statistics. The variables evaluated were the dimensions that make up the environmental behavior: affective, conative and active cognitive dimension. The results of the environmental awareness of people in the urban area (84.7%) are better than that of the peri-urban area (65.8%). Regarding the environmental dimensions, the following were taken: affective dimension, urban area (30.62%) and peri-urban area (26.0%), as a high rating. Greater results are regular assessment. Cognitive dimension, we have, urban area (71.52%) and peri-urban area (58.8%). Conative dimension, urban area (94.1%) and peri-urban area (80.8%). Active dimension, values are presented for: peri-urban area (56.22%) and urban area (31.8%) It is concluded that the environmental awareness of the urban area is higher than that of the peri-urban area; the affective dimension of the urban is higher than the periurban; the cognitive dimension the urban area is greater than the peri-urban; the conative dimension in the urban and peri-urban areas are almost the same; the periurban active dimension reached higher scores than the urban one.